Identifikasi Komoditas Unggulan Perikanan Laut di Kecamatan Tungkal Ilir Kabupaten Tanjung Jabung Barat - Sukma Bakti; Herlina Herlina (Universitas Batanghari Jambi, 2020)
Sea fisheries production become a serious problem for the people of Kampung Nelayan Village, Tungkal ilir District, regarding to improve their welfare. This study aims to analyze the leading commodity in marine fisheries in Tungkal Ilir District. The analytical methods used are the location quetient and shift share. The results of the location quetient analysis showed that the basic commodity of marine fisheries are mackerel, white pomfret, black pomfret, croackers, fourfinger threadfin, double spotted queenfish, mullet, eel tailed catfish, white shrimp and other shrimp. The results of shift share analysis showed that the commodities categorized as winner quadrant are croackers, fourfinger threadfin, sweet lips, daggertooth pike conger fish, grouper, fish belt, stingray, pink/yellow-white shrimp. Based on the combined analysis result, the leading commodities are croackers and fourfinger threadfin. They has ideal competitiveness also expected to be developed further and have an impact on increasing the income of fishermen.